KERIS MAGIC BOOK SEBAGAI PENGENALAN KERIS KEPADA REMAJA - Asmoro Nurhadi Panindias (Ornamen, 2014)
Kris as a weapon is a symbol of traditional aesthetic, which has a ceremonial significance and superiormetallurgical technology, in addition to valuable antiques. Kris is a masterpiece of cultural heritage of Indonesiaare highly valued and able to amaze the world community. Keris recognized as World Heritage and awardedthe Masterpiece of the Oral and Intangible Heritage of Humanity by UNESCO, which is a testament to theworldwide recognition of the kris as a masterpiece of Indonesian heritage. Books about the Kris with a targetaudience of teenagers has not been published. Though the nationâ€™s youth as the next generation, is expectedto be able to preserve and continue the existence of the kris as part of the cultural heritage of the archipelago.â€œKeris Magic Bookâ€ is a combination of conventional books with augmented reality technology. Narrative,illustration and paper as part of a conventional book will be added to the virtual object, when the book iscombined with augmented reality technology. This book will reduce the lack of books in digital technologyand so is its opposite. Kris will be shown with illustrations, 3D objects, sound and movie. One of the advantagesâ€œKeris Magic Bookâ€ is a case to solve communication and information between the presence of kris with aninterest in youth to learn it. Bring up a graphic design media in the form of a book with augmented realityapplication that is able to appreciate about the kris, not only physically but also in the philosophy of eachsymbol in the kris.Keywords: Kris, augmented reality, magic book.